2008
DOI: 10.1002/clen.200700179
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Airborne Microbial Concentrations and Diversity at Landfill, Urban and Rural Sites

Abstract: Microbes are present everywhere in outdoor air. However, the general characterization of outdoor air mycobiota and bacterial flora is incomplete. In this study, seasonal variations in outdoor air microbial concentrations and differences between a landfill, urban and rural sites were compared. Samples were collected monthly for a period of one year. Airborne dust samples were collected onto polyvinyl chloride filters. Filter samples were analyzed for ergosterol, and 14 species or assay groups of fungi and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…It has often been found that numbers are greatest in summer and autumn (Bovallius et al, 1978;Jones and Cookson, 1983;di Giorgio et al, 1996;Tong and Lighthart, 1999;Fang et al, 2007;Kaarkainen et al, 2008), although exceptions exist; Fahlgren et al (2010) found that bacteria counts at a coastal site were highest in winter, which they attributed to a strong winter marine sea spray source. Over a period of 1 d, bacteria have usually been observed to exhibit a peak airborne concentration in the morning and evening (Lighthart and Shaffer, 1995;Shaffer and Lighthart, 1997;Fang et al, 2007).…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…It has often been found that numbers are greatest in summer and autumn (Bovallius et al, 1978;Jones and Cookson, 1983;di Giorgio et al, 1996;Tong and Lighthart, 1999;Fang et al, 2007;Kaarkainen et al, 2008), although exceptions exist; Fahlgren et al (2010) found that bacteria counts at a coastal site were highest in winter, which they attributed to a strong winter marine sea spray source. Over a period of 1 d, bacteria have usually been observed to exhibit a peak airborne concentration in the morning and evening (Lighthart and Shaffer, 1995;Shaffer and Lighthart, 1997;Fang et al, 2007).…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…The number and composition of airborne microorganisms have increased in the urban and rural areas 1 .The presence of microorganisms depends on seasonality, geographical conditions, meteorological factors, type of sources 2, 3 4 , and air pollution 5 .Airborne microorganisms may contributẽ 20%, 22% and 10% of the total particulate matters in the remote continental, populated-continental, and remote maritime environments, respectively 6 . The concentrations and composition of airborne microorganisms undergoes daily, weekly and seasonally changes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sampling location characteristics (e.g., altitude and urban versus rural sites) and temporal aspects have a large influence on the number and identity of collected bacteria. Nevertheless, some general trends can be outlined based on published sources: bacterial CFU counts are often higher in urban than in rural sites when samples are taken in the same geographic region (11,18), bacterial CFU counts seem generally lower in coastal than inland areas (11,43), and both fungi and bacteria occur in higher numbers in the air in summer and autumn in both rural and urban environments (11,18,20,27). Bacterial abundance also varies diurnally: in urban and rural locations, the highest CFU counts have been found in the morning and evening (20,29,43).…”
mentioning
confidence: 99%